Revisiting Educational Development in Himachal Pradesh - Negi, Suman (JOURNAL OF INDIAN EDUCATION, 2017)
Himachal Pradesh has witnessed tremendous progress in the educational development in a relatively short span of time. The State has achieved nearly 100 per cent universal elementary education and has one of the lowest dropout rates at the national level. The challenge at present is lower levels of participation at the higher education level, which could mainly be attributed to lesser number of institutions available. The impressive results in educational participation and access are mainly attributed to its efficiently run and managed government schooling system. However, the success of government schools seems to be losing its sheen as private schooling revolution is taking over the State-run schools rapidly. The share of government school participation has decreased sizeably over the decade, whereas the share of private school participation has increased. This is a serious concern and the government schooling system needs to be made more accountable and all stakeholders including teachers, administrators, policymakers, community and parents need to take active responsibilities.